Importance of genetic evaluation and preconception counseling in a case of Prader-Willi/Angelman syndrome - Guerrero Marín, María Angélica (2024)
Objective: To report a case of prenatal diagnosis of Prader-Willi/Angelmansyndrome using microarray. A review of the literature is made and the importanceof preconceptional genetic counselling is highlighted. Case report: A 30-year-oldfemale patient G2P1001 underwent genetic screening ultrasound at 11-14 weeks,in which increased nuchal sonolucence was detected in percentile greater than99. She was taken to amniocentesis for microarray in amniotic fluid at 21 weekswhose result was chromosomal deletion 15q11.2q13.1 compatible with Prader-Willi/Angelman Syndrome. The patient was accompanied by maternal-fetal medicineand was informed about the prenatal diagnosis. The patient chose to terminate thepregnancy voluntarily. No anatomopathological study of the fetus was performed.Conclusions: Although in Colombia sentence C-355 of 2006 establishes the threegrounds under which voluntary termination of pregnancy is legally available, it doesnot emphasize the importance of carrying out an anatomopathological study offetuses with a prenatal diagnosis of a genetic pathology. This does not allow for agenotype-phenotype correlation, nor does it allow parents to receive preconceptiongenetic counseling for future pregnancies.